2017
DOI: 10.2147/ndt.s127863
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis in behavioral variant frontotemporal dementia

Abstract: BackgroundDementia is generally characterized by cognitive impairment that can be accompanied by psychotic symptoms; for example, visual hallucinations are a core feature of dementia with Lewy bodies, and delusions are often seen in Alzheimer’s disease. However, for behavioral variant of frontotemporal dementia (bvFTD), studies on the broad spectrum of psychotic symptoms are still lacking. The aim of this study was to systematically and prospectively subtype the wide spectrum of psychotic symptoms in probable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 40 publications
2
24
1
2
Order By: Relevance
“…According to current diagnostic criteria, a primary psychiatric diagnosis is still considered an exclusion criterion for FTD . On the contrary, our results and those of other recent studies suggest that including more neuropsychiatric symptoms in the clinical assessment might improve diagnostic accuracy.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…According to current diagnostic criteria, a primary psychiatric diagnosis is still considered an exclusion criterion for FTD . On the contrary, our results and those of other recent studies suggest that including more neuropsychiatric symptoms in the clinical assessment might improve diagnostic accuracy.…”
Section: Discussioncontrasting
confidence: 62%
“…Mutations in genes, such as chromosome 9 open reading frame 72 ( C9orf72 ), progranulin ( GRN ), and microtubule associated protein tau ( MAPT ) have been identified in about 25% of patients with FTD . More recently, neuropsychiatric symptoms, such as psychosis and depressed mood, have been recognized to be part of the early clinical presentation of FTD, both in C9orf72 repeat expansion carriers and noncarriers . Due to the clinical variability and overlap of symptoms with primary psychiatric diseases and other neurodegenerative diseases, such as Alzheimer's disease, and given the lack of biomarkers, it remains challenging to diagnose FTD accurately in a clinical setting.…”
mentioning
confidence: 99%
“…Previous studies have shown different neurocognitive progression according to the major type of symptom in FTD (Santamaría-García et al, 2016). A broad range of NPS in both AD and FTD has been described including delusions and sensory-perceptual alterations (hallucinations and illusions; Rubin et al, 1988; Van Dam et al, 2016; Gossink et al, 2017), as well as conduct problems (Santamaría-García et al, 2016; Van Dam et al, 2016), depressive and anxiety symptoms (Brodaty et al, 2015; Sellami et al, 2018), sleep problems (Mander et al, 2016; Merrilees et al, 2014) and eating changes (Ahmed et al, 2015; Ringman et al, 2015). Regarding the psychotic symptoms (including delusions and sensory-perceptive alterations such as hallucinations and illusions), previous studies have reported that those symptoms can appear in both AD and FTD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, particularly FTLD patients with a concomitant motor neuron disease have been observed to present with prominent psychotic symptoms in the prodromal stage of the disease [65,66]. Previous studies also indicate that up to one third of the bvFTD patients will develop psychotic symptoms at some stage of the disease [23,29,67]. Nevertheless, these symptoms are not part of the current diagnostic bvFTD criteria [2], and a significant number of bvFTD patients will receive a psychiatric diagnosis in the early stages of the disease [65,68].…”
Section: Discussionmentioning
confidence: 99%